2010
DOI: 10.1007/s00468-010-0455-4
|View full text |Cite
|
Sign up to set email alerts
|

Single primer amplification reaction (SPAR) reveals intra-specific natural variation in Prosopis cineraria (L.) Druce

Abstract: Prosopis cineraria, an important multipurpose tree and vital component of the otherwise fragile ecosystem of arid and semiarid regions of India. It is highly drought tolerant and sprouts profusely during the extreme dry summer months when most other trees are leafless. P. cineraria is known to exhibit comparable genetic variations at intra-specific and inter-population levels reflected through morphological and cytogenetical diversity in regions, where this plant grows naturally. In the present study, single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
4
29
1
Order By: Relevance
“…The commonly used polymerase chain reaction (PCR)-based DNA marker for Musa variability studies are restriction fragment length polymorphism (RFLP; Jarret et al 1992), RAPD (Jarret et al 1993;Onguso et al 2004), microsatellites (Lagoda et al 1998;Creste et al 2003Creste et al , 2004, and AFLP (Wong et al 2002). Lately, the single primer amplification reaction (SPAR) method i.e., the combination of RAPD, ISSR and DAMD markers is becoming an important tool for genetic diversity analysis in plants and they collectively provide a comprehensive description of the nature and the extent of diversity, its genetic relationship and germplasm management (Bhattacharya et al 2005;Kumar et al 2011Kumar et al , 2013Ranade et al 2009;Sharma et al 2010Sharma et al , 2011. This could be of the fact that RAPD amplicons are generated from amplifications representing widely distributed regions of the genome, whereas ISSR and DAMD amplicons are generated from the microsatellite-rich portions of the genome (Kumar et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used polymerase chain reaction (PCR)-based DNA marker for Musa variability studies are restriction fragment length polymorphism (RFLP; Jarret et al 1992), RAPD (Jarret et al 1993;Onguso et al 2004), microsatellites (Lagoda et al 1998;Creste et al 2003Creste et al , 2004, and AFLP (Wong et al 2002). Lately, the single primer amplification reaction (SPAR) method i.e., the combination of RAPD, ISSR and DAMD markers is becoming an important tool for genetic diversity analysis in plants and they collectively provide a comprehensive description of the nature and the extent of diversity, its genetic relationship and germplasm management (Bhattacharya et al 2005;Kumar et al 2011Kumar et al , 2013Ranade et al 2009;Sharma et al 2010Sharma et al , 2011. This could be of the fact that RAPD amplicons are generated from amplifications representing widely distributed regions of the genome, whereas ISSR and DAMD amplicons are generated from the microsatellite-rich portions of the genome (Kumar et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported the efficiency of using both types of markers (Ranade et al, 2009;Elmeer and Almalki, 2011;Mani et al, 2011;Sharma et al, 2010Sharma et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Souza Neto et al Mani et al, 2011;Sharma et al, 2010Sharma et al, , 2011, particularly for those species that have not been well-studied or those for which specific molecular markers had not been developed. Sharma et al (2011) reported the efficiency of reactions involving 1 primer, such as the random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) methods, for analyzing genetic diversity in higher plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although meiotic analysis, including data on chromosome associations and recombination frequencies, did throw some light on probable genetic diversity available in the species, the same needs to be corroborated by molecular analysis of the genome. Recently, Sharma et al (2010Sharma et al ( , 2011aSharma et al ( , b, 2012 has proved the utility of single primer amplification reaction (SPAR) methods for the analysis of genetic variation in desert trees as well as several other plant taxa. It is further concluded that B. serrata (n = 22) and its diversification is helped by genetic/genic alteration, extensive outbreeding, distally localized recombinations, etc.…”
Section: Discussionmentioning
confidence: 99%